Comparative study of transthoracic ultrasound and chest X-ray in the postoperative period of thoracic surgery - Ariza, Julián A.; Martínez, Manuel J. Muñoz; Olivera, María José; Balsalobre, Ramón Moreno (International Surgery Journal, 2017)
Background: Chest radiography is currently the reference technique in postoperative follow-up of thoracic surgery. However, routine use (almost daily) has been repeatedly questioned. Moreover, transthoracic ultrasound, besides being a useful technique in pleuropulmonary pathology offers additional advantages over the radiograph. The aim of this study is to analyse the diagnostic agreement between radiographic and ultrasound techniques in the postoperative follow-up of thoracic surgery. Methods: Observational, prospective study, in the postoperative period of thoracic surgery, to study the concordance between the ultrasound and radiographic findings. Sixty patients were evaluated during the postoperative period with the two diagnostic tests, first the transthoracic ultrasound of the 2 hemithorax and then the chest radiograph. Each patient had an ultrasound and an X-ray. The sonographer and radiologist have independently assessed the occurrences of pneumothorax, pleural effusion, pulmonary consolidation, and interstitial pattern. Results: The Cohen kappa index for pneumothorax was 0.706 (p <0.001), for pleural effusion 0.588 (p <0.001), for interstitial pattern 0.474 (p <0.001) and for pulmonary consolidation 0.282 (p 0.002). Conclusions: The diagnostic concordance between radiographic and ultrasound techniques in the postoperative period of thoracic surgery is substantial for pneumothorax and pleural effusion, moderate for interstitial pattern, and fair for pulmonary consolidation.